Replication Data for: Forage quality in tundra grasslands under herbivory: Silicon-based defences, nutrients, and their ratios in grasses - Petit Bon, Matteo; Inga, Katarina Gunnarsdotter; Utsi, Tove Aagnes; Jónsdóttir, Ingibjörg Svala; Bråthen, Kari Anne (DataverseNO, 2021)
Dataset used to ask (i) to what extent herbivores (small-rodent winter disturbance and reindeer summer herbivory) modify leaf Silicon-based defence levels in grasses and (ii) to what extent such changes can alter grass quality in terms of leaf Silicon:Nitrogen and Silicon:Phosphorus ratios in tundra grasslands throughout a short Arctic summer.